Improving Student Learning Outcomes through Interactive Learning Videos on Plant Parts for Fourth Grade Elementary School Students - Ni Nyoman Ayu Trisnayani; I Kadek Suartama; Ni Made Dainivitri Sinta Sari (Indonesian Values and Character Education Journal, 2025)
This study is motivated by the low learning outcomes of students on the topic of plant parts in fourth-grade elementary school, which is caused by the limited use of engaging learning media that suit the students’ characteristics. The purpose of this study is to develop interactive learning videos to improve students’ learning outcomes. The development model used is the ADDIE model (Analysis, Design, Development, Implementation, Evaluation). The subjects of this study were 18 fourth-grade students. The data collection methods and instruments used in this development research included questionnaires and multiple-choice tests. The data analysis techniques employed were qualitative descriptive, quantitative, and inferential. The results of the study indicate that the interactive learning videos developed were effective in improving students’ learning outcomes, as evidenced by the increase in average scores and positive responses from the students regarding the learning process. The implications of this study suggest that interactive video media can be an appropriate solution for teaching science, especially for visually-oriented topics, and can encourage teachers to be more innovative in designing technology-based learning.